2006
DOI: 10.1007/s11557-006-0514-9
|View full text |Cite
|
Sign up to set email alerts
|

UV triggers the synthesis of the widely distributed secondary lichen compound usnic acid

Abstract: Synthesis of the cortical dibenzofuran derivative usnic acid and the medullary depsidone salazinic acid was studied in Xanthoparmelia stenophylla thalli from which the compounds had been removed by acetone rinsing prior to a 21-day field experiment with UV absorbing and transmitting screens. Natural levels of ultraviolet radiation clearly induced the re-synthesis of usnic acid. The resynthesis was boosted by the addition of ribitol, the carbohydrate delivered from the Trebouxia photobiont to the mycobiont. Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 37 publications
1
60
0
Order By: Relevance
“…Usnic acid is a yellowish dibenzofuran, exclusive to lichen-forming fungi and widely distributed in the vegetative and reproductive structures of several species (e.g., species of genera Lecanora, Ramalina) ( Ingólfsdóttir, 2002;Liao et al, 2010). It is well known for antibacterial and antifungal properties (and for antiprotozoal, antiviral, antiproliferative, antiinflammatory, analgesic, antipyretic, antitumor activities) which have been mostly studied for potential therapeutic applications ( Cocchietto et al, 2002;Ingólfsdóttir, 2002), and is also known to play UV protection of thalli ( McEvoy et al, 2006). Norstictic acid is a depsidone, exclusive to lichen-forming fungi (e.g., in species of genera Buellia, Lecanora, Porpidia, Rhizocarpon), which is mostly deposited as crystals in the apoplast and soluble in water in a small proportion, being likely involved in the metal uptake and homeostasis of lichens ( Hauck et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Usnic acid is a yellowish dibenzofuran, exclusive to lichen-forming fungi and widely distributed in the vegetative and reproductive structures of several species (e.g., species of genera Lecanora, Ramalina) ( Ingólfsdóttir, 2002;Liao et al, 2010). It is well known for antibacterial and antifungal properties (and for antiprotozoal, antiviral, antiproliferative, antiinflammatory, analgesic, antipyretic, antitumor activities) which have been mostly studied for potential therapeutic applications ( Cocchietto et al, 2002;Ingólfsdóttir, 2002), and is also known to play UV protection of thalli ( McEvoy et al, 2006). Norstictic acid is a depsidone, exclusive to lichen-forming fungi (e.g., in species of genera Buellia, Lecanora, Porpidia, Rhizocarpon), which is mostly deposited as crystals in the apoplast and soluble in water in a small proportion, being likely involved in the metal uptake and homeostasis of lichens ( Hauck et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The 5 degree latitude difference in this study resulted in a temperature and daylength difference. But the change in UV light levels was not likely to be sufficient to produce changes in cortical compounds as was evident for McEvoy et al (2006) and Bjerke et al (2002), where increased light gradients were measured from forested locations to exposed alpine locations. In this study the habitat was relatively constant with open jack pine bedrock of the Precambrian shield regardless of whether the location was in the northern or southern regions.…”
Section: Effect Of Environmental Change On Secondary Metabolite Produmentioning
confidence: 99%
“…These observations suggest that environmental parameters may trigger the production of certain compounds in some species. Numerous studies have shown a correlation between light levels and production of usnic acid (Armaleo et al, 2008;McEvoy et al, 2007a;Rundel, 1969;Bjerke et al, 2002;McEvoy et al, 2006) or other compounds (Armaleo et al, 2008;Bjerke et al, 2002;McEvoy et al, 2007b) within thalli. The amount of atranorin in the cortex of Parmotrema hypotropum was shown to correlate positively with the amount of yearly light reaching the thallus (Armaleo et al, 2008).…”
Section: Effects Of Abiotic Parameters: Temperature Light Ph and Hmentioning
confidence: 99%
“…This leads the cell aggregates for deprivation of required nutrient and stops the production of desirable lichen compounds. Many authors suggested that production of lichen substances have strong correlation with the light intensity for a longer period (Rundel 1969;Fahselt 1981;Hamada 1991;Bjerke et al 2002Bjerke et al , 2004McEvoy et al 2006McEvoy et al , 2007aArmaleo et al 2008). Brodo (1973) reviewed the significance of the substratum to lichen and reported different tree bark and rock types can have different pHs, nutrients, and water holding capacity makes different lichen species to grow (Fig.…”
Section: Effects Of Temperature Ph Light and Humiditymentioning
confidence: 99%